2021
DOI: 10.1177/03000605211019663
|View full text |Cite
|
Sign up to set email alerts
|

High retinoic acid receptor-related orphan receptor A gene expression in peripheral blood leukocytes may be related to acute myocardial infarction

Abstract: Objective This study aimed to investigate whether differential expression of the retinoic acid receptor-related orphan receptor A ( RORA) gene is related to occurrence of acute myocardial infarction (AMI). Methods This was a retrospective study. White blood cells of 93 patients with acute myocardial infarction and 74 patients with stable coronary artery disease were collected. Reverse transcription quantitative polymerase chain reaction and western blotting were used to measure RORA mRNA and protein expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…The RORA gene was reported to be upregulated in patients with AMI (just like the results of qRT-PCR), which might suppress hypoxic injury of cardiomyocyte cells in AMI by inhibiting oxidative stress and apoptosis. 69,70 Meanwhile, the diagnostic significance of FASLG was detected in AMI, 10 which was consistent with our findings, indicating that these biomarker genes were still worthy of study in AMI.…”
Section: Discussionsupporting
confidence: 88%
“…The RORA gene was reported to be upregulated in patients with AMI (just like the results of qRT-PCR), which might suppress hypoxic injury of cardiomyocyte cells in AMI by inhibiting oxidative stress and apoptosis. 69,70 Meanwhile, the diagnostic significance of FASLG was detected in AMI, 10 which was consistent with our findings, indicating that these biomarker genes were still worthy of study in AMI.…”
Section: Discussionsupporting
confidence: 88%
“…RORα plays an essential role in the regulation of cardiovascular function including circadian rhythm, development, and metabolism [183][184][185]. One human retrospective study found that RORα mRNA expression levels in patients with acute myocardial infarction is significantly higher than that in patients with stable coronary artery disease [186]. Serum antibody levels of Claudin domain containing 1 (CLDND1)-derived peptides are elevated in patients with cerebral infection, CVDs or diabetes mellitus as compared to healthy controls.…”
Section: Retinoic Acid-related Orphan Receptor (Ror)mentioning
confidence: 99%
“…With respect to translational approaches, the REVERB agonist SR9009 when given early after ischemia, in mice, improved ischemia-perfusion-related remodeling and cardiac function ( Reitz et al, 2019 ). In addition to REVERB agonists, attention is currently being applied to the development of RORa ligands for cardiovascular disease, for example, they are overexpressed in acute myocardial infarction ( Meng et al, 2021 ).…”
Section: Circadian Disruption In Vascular Diseasementioning
confidence: 99%